Dyslipidemia in type II diabetes mellitus: Pathophysiology and therapeutic approach - Adiwijono Adiwijono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Dyslipidemia occurs commonly in type II diabetes mellitus. Although all classes of lipoprotein may be involved, the most common lipid abnormality is increased triglycerides levels. The metabolic abnormalities associated with diabetes per se can have marked effects on serum lipids. In liver and adipose tissue, insulin has a key regulatory role of both lipid and carbohydrate metabolism pathways. If insulin secretion or action is abnormal, changes in fat and glucose metabolism will result. However, which changes will occur, is largely determined by the type of diabetes, the degree of insulin deficiency and the relative glycamic control. In many type II diabetes mellitus, it is likely that the etiology of dyslipidemia are multifactorial.There are three possible mechanisms that cause dyslipidemia in diabetes mellitus more atherogenic, i.e. glycosylation, oxidation and carbamylation processes. Since dyslipidemia and other risk factors for vascular diseases (obesity, hypertension, smoking) are frequently present, the approach to management must be broadly based.Association between diabetes mellitus and triglycerides, including relationship between disturbances of carbohydrate and lipid metabolism, provide the rational use of the antilipidemic agents, diet and sport.Key Words: diabetes mellitus - dyslipidemia - insulin - atherosclerosis - hypolipidemic agents